PENDIDIKAN AKHLAK PERSPEKTIF AL GHAZALI DALAM MENANGGULANGI LESS MORAL VALUE - Zaenol Fajri; Sayyidatul Mukarromah (EDURELIGIA: Jurnal Pendidikan Agama Islam, 2021)
This study aims to provide an overview of the urgency of moral education as shield from the problem of students' lack of moral character. Islamic education has very strategic position in the development of human nature. Therefore, educational studies have attracted many experts, one of which is Al-Ghazali. In theory, introducing how to still religious values in overcoming students' lack of moral attitudes. This research uses descriptive-analysis research, with technical content analysis. This study uses a library research approach (literature review). The results showed that the opinion of Imam al Ghazali about moral education is to eliminate despicable traits and instill praiseworthy qualities to make human beings kamil and get closer to ALLAH SWT so that humans can get happiness in the world and the here after.